Pharmacological correction of neurogenic lower urinary tract dysfunction in children - T.P. Borysova; T.V. Fedko; T.A. Nikolaenko; M.V. Boyko; O.A. Ostrovskaya; A.V. Obertinsky; K.V. Shevchenko (Zaslavsky O.Yu., 2020)
Background. The purpose was to evaluate the effectiveness and safety of pharmacological correction of neurogenic lower urinary tract dysfunction in children using noophen (phenibut) in combination with a prophylactic dose of furamag. Materials and methods. Twenty-four children aged 5 to 8 years with complaints of frequent urination in the daytime were under observation. All patients underwent neurological and uronephrological examination. The history of the disease, somatic status, general urine analysis and bacteriological culture of urine were evaluated. To assess the urodynamics of the lower urinary tract, a diary of urination, ultrasound examination of the kidneys and bladder, and uroflowmetry were studied. An assessment of the neuropsychiatric status was carried out, namely: symptoms of impaired attention, hyperactivity and impulsivity. For 28 days, children were prescribed standard urotherapy and noophen, a prophylactic dose of furamag, and group B vitamins. Results. After examination, a hyperactive bladder was diagnosed in 15 (62.5 %) and dysfunctional urination - in 9 (37.5 %) children. At the end of treatment, a positive dynamics in the clinical picture was observed in 21 (87 %) patients, of which 9 (38 %) fully recovered, and partial improvement was observed in 12 (49 %) children. The lack of effect from the therapy was observed in 3 (13 %) children. The change in the frequency of urination during therapy was characterized by a significant decrease in the first two weeks of treatment from 16.00 ± 1.35 to 11.10 ± 0.57 (p < 0.001). At the end of therapy, the frequency of urination was 8.90 ± 0.35 (p < 0.001). Urges to urinate were practically eliminated; urinary incontinence was not observed by the end of treatment course. After a course of treatment, the effective bladder volume increased by 38.9 % (p < 0.001). The positive impact on urodynamic indicators was shown: an increase in urination volume (by 35.1 %, p < 0.001), maximal (by 28.8 %, p < 0.002) and average urine flow rate (by 53.3 %, p < 0.001). During the observation, the examined children did not have a single case of urinary tract infection. We succeeded to prove the corrective effect of noophen drug on the symptoms of inattention and, to a greater extent, on hyperactivity-impulsivity; as well as the significance of the connection between the effectiveness of treatment for lower urinary tract dysfunction and neuropsychiatric positive dynamics (p < 0.004). A favorable safety profile of noophen and furamag preparations is shown. Conclusions. The therapeutic efficacy and safety of noophen in combination with the prophylactic dose of furamag for neurogenic lower urinary tract dysfunction in children was established, which was confirmed by a positive dynamics of clinical disease symptoms, urodynamic indicators, a decrease in the symptoms of inattention, hyperactivity and impulsivity.